Correlation between discharged worms and fecal egg counts in human clonorchiasis. - Jae-Hwan Kim; Min-Ho Choi; Young Mee Bae; Jin-Kyoung Oh; Min Kyung Lim; Sung-Tae Hong (Public Library of Science (PLoS), 2011)
BACKGROUND: Stool examination by counting eggs per gram of feces (EPGs) is the best method to estimate worm burden of Clonorchis sinensis in infected humans. The present study investigated a correlation between EPGs and worm burden in human clonorchiasis. METHODS AND FINDINGS: A total of 60 residents, 50 egg-positive and 10 egg-negative, in Sancheong-gun, Korea, participated in this worm collection trial in 2006-2009. They were diagnosed by egg positivity in feces using the Kato-Katz method. After administration of praziquantel, they were purged with cathartics on the next day, and then discharged adult worms were collected from their feces. Their EPGs ranged from 0 to 65,544. Adult worms of C. sinensis were collected from 17 egg-positive cases, and the number of worms ranged from 1 to 114 in each individual. A positive correlation between EPGs and numbers of worms was demonstrated (r = 0.681, P<0.001). Worm recovery rates were 9.7% in cases of EPGs 1-1,000 and 73.7% in those of EPGs over 1,000. No worms were detected from egg-negative subjects. Maximum egg count per worm per day was roughly estimated 3,770 in a subject with EPGs 2,664 and 106 collected worms. CONCLUSIONS: The numbers of the worms are significantly correlated with the egg counts in human clonorchiasis. It is estimated that at least 110 worms are infected in a human body with EPGs around 3,000, and egg productivity of a worm per day is around 4,000.